Pengaruh Struktur Aset, Resiko Bisnis, Pajak dan Likuiditas terhadap Keputusan Pendanaan pada Perusahaan Kawi - Sherina Sherina; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Ekonomis: Journal of Economics and Business, 2022)
In running a company, funding is needed for all company activities. Funding decisions have a very important role in the survival of a company. There are two sources of funding in the company, namely internal and external sources. Internal sources are retained earnings and external sources are debt and issued shares. Company’s manager must consider which sources would have the best result on the company. The analytical technique used in this research is a comparative descriptive analysis technique. Primary datas were collected through interviews and observations while secondary data were obtained from literatures related to the research topic. Asset structure, business risk, tax, liquidity and funding decisions are used as research objects. The results shows that asset structure, risk and liquidity had no effect on funding decisions at Kawi company. Taxes had an effect on funding decisions at Kawi company. Asset structure, business risk, tax and liquidity together have no effect on funding decisions at Kawi company.